New economic thinking and real estate - Myers, Danny (John Wiley & Sons Ltd, 2016)
"New Economic Thinking and Real Estate offers a modern and distinctive approach to forecasting and understanding property markets. With this book, students will develop an intuitive ability to interpret economic indicators and acquire the confidence to assess property markets. The book is divided into three parts: Part A: Resource choices - deals with microeconomics; Part B: Financial Systems - seeks to make sense of the macroeconomic scene and Part C: Measuring and Forecasting"